Percutaneous electrical nerve field stimulation compared to standard medical therapy in adolescents with functional abdominal pain disorders - Santucci, Neha R.; Sahay, Rashmi; El-Chammas, Khalil I.; Graham, Kahleb; Wheatley, Mikaela; Vandenbrink, Madeleine; Hardy, Jennifer; Fei, Lin (Frontiers in Pain Research, 2023)
Introduction: Standard medical therapy (SMT) in children with functional abdominal pain disorders (FAPD) includes cyproheptadine and amitriptyline. While percutaneous electrical nerve field stimulation (PENFS) has shown benefit, no study has compared outcomes of PENFS to SMT. We aimed to examine changes in abdominal pain, nausea and disability before and after treatment and compare outcomes between treatments. Methods: The records of FAPD patients ages 11-21 years, treated with 4 weeks of PENFS, cyproheptadine or amitriptyline were reviewed. Outcomes were evaluated using validated questionnaires [Abdominal Pain Index (API), Nausea Severity Scale (NSS), and the Functional Disability Inventory (FDI)] at baseline and follow-up within 3 months (FU). Result: Of 101 patients, 48% received PENFS, 31%cyproheptadine and 21% received amitriptyline. Median ages were 17 (15-19), 16 (15-18) and 15 (11-16) years respectively and the majority were females (75%, 90% and 52% respectively). In the PENFS group, API (p=0.001), NSS (p=0.059) and FDI (p=0.048) were significantly lower at FU. API (p=0.034) but not NSS and FDI (p>0.05) decreased significantly at FU in the amitriptyline group. API, NSS and FDI did not change significantly with cyproheptadine at FU (p>0.05). FU API scores were lower in PENFS versus cyproheptadine (p=0.04) but not versus amitriptyline (p=0.64). The FDI scores were significantly lower in the amitriptyline vs. cyproheptadine group (p=0.03). Conclusion: Therapy with PENFS showed improvements in abdominal pain, nausea and disability while amitriptyline showed improvements in abdominal pain within 3 months of treatment. PENFS was more effective than cyproheptadine in improving abdominal pain. Amitriptyline improved disability scores more than cyproheptadine and showed promise for treatment. PENFS may be a good non-pharmacologic alternative for FAPD.